Changes in elastic wave velocity and rock microstructure due to basalt‐CO2‐water reactions. Issue 8 (9th August 2013) - Adam, Ludmila; van Wijk, Kasper; Otheim, Thomas; Batzle, Michael
Abstract : [1] The chemical interaction between carbon dioxide, water, and basalt is a common process in the earth, which results in the dissolution of primary minerals that later precipitate as alteration minerals. This occurs naturally in volcanic settings, but more recently basalts have been suggested as reservoirs for sequestration of anthropogenic CO2 . In both the natural and man‐made cases, rock‐fluid reactions lead to the precipitation of carbonates. Here, we quantify changes in ultrasonic wave speeds, associated with changes in the frame of whole‐rock basalts, as CO2 and basalt react. After 30weeks of reactions and carbonate precipitation, the ultrasonic wave speed in dry basalt samples increases between 4% and 20% and permeability is reduced by up to an order of magnitude. However, porosity decreases only by 2% to 3%. The correlation between significant changes in wave speed and permeability indicates that a precipitate is developing in fractures and compliant pores. Thin sections, XRF‐loss on ignition, and water chemistry confirm this observation. This means time‐lapse seismic monitoring of a CO2 ‐water‐basalt system cannot assume invariance of the rock frame, as typically done in fluid substitution models. We conclude that secondary mineral precipitation causes a measurable change in the velocities of elastic waves in basalt‐water‐CO2 systems, suggesting that seismic waves could be used to remotely monitor future CO2 injection sites. Although monitoring these reactions in the field with seismic waves might be complicated due to the heterogeneous nature of basalt, quantifying the elastic velocity changes associated with rock alteration in a controlled laboratory experiment forms an important step toward field‐scale seismic monitoring. Key Points: Experiments show whole-basalt reactions with CO2 precipitate carbonates Elastic waves and permeability are sensitive to a small volume of precipitate The basalt rock frame changes over time if in contact with carbonic acid